IR radiation-induced changes in the optical and registration properties of a CR-39 nuclear track detector. (July 2019) - Saad, A.F.; Ibraheim, Mona H.; Hamada, Mona
Abstract: The UV–Vis (ultraviolet–visible) spectra and etching characteristics have been studied of poly allyl diglycol carbonate (PADC, a form of the CR-39 polymer) detector films after exposure to 250 W IR-radiation lamp for various times ranging from 1 to 40 min. Etching experiments were carried out on the IR-exposed CR-39 detectors after alpha particle irradiation using a 241 Am source. The bulk and track etch rates were measured using the weight loss and alpha track diameter methods, respectively, as well as the sensitivity, the detection efficiency, and the critical angle, were also determined. The optical band gap for both indirect and direct transitions was calculated based on the absorption edge of the UV spectra of the pristine and variously IR-exposed detectors. UV–Vis spectra of pristine and IR irradiated PADC polymer films exhibit a decreasing trend in the optical band gap, direct and indirect transitions, ranging from 4.64 ± 0.23, 3.85 ± 0.20 to 3.40 ± 0.12 and 3.04 ± 0.11 eV, correspondent to IR exposure time from 0 to 40 min, respectively. This decline in the optical band gap with increasing IR exposure time has been discussed on the basis of IR irradiation-induced defects in PADC. Further etching measurements, of 3 and 9 h etching times, confirmed a decrease in sensitivity from 1.86 ± 0.06 to 1.05 ± 0.03 and from 1.78 ± 0.06 to 1.03 ± 0.03 as well as in detection efficiency from 46.2 ± 1.45 to 4.68 ± 0.12 and from 43.91 ± 1.50 to 2.98 ± 0.09 (%) correspondents to IR exposure time from 0 to 40 min, respectively, in IR irradiated CR-39 polymer detector. Highlights: Optical properties of pristine and IR-irradiated CR-39 detectors were investigated. IR radiation-induced changes in the CR-39 detector were observed. IR-exposed CR-39 detectors provide spectroscopic energy data. CR-39 detectors are exposed to IR radiation for sensitivity testing. Feasibility of achieving low sensitivity with high IR exposure was demonstrated.